ВИКОРИСТАННЯ ПЕДАГОГІЧНИХ ТЕХНОЛОГІЙ В ПРОЦЕСІ РЕАЛІЗАЦІЇ ПРОФІЛЬНОГО НАВЧАННЯ В ПРИВАТНИХ ШКОЛАХ УКРАЇНИ (Педагогіка вищої та середньої школи, 2007)
This article is devoted to the problem of realization of pedagogical technologies at the process of profile education at the private schools of Ukraine. The author determines the main characteristics and specific factors of pedagogical technologies at the educational process at the private schools of Ukraine.